2021
DOI: 10.1126/sciadv.abf1600
|View full text |Cite
|
Sign up to set email alerts
|

IgSF11 homophilic adhesion proteins promote layer-specific synaptic assembly of the cortical interneuron subtype

Abstract: The most prominent structural hallmark of the mammalian neocortical circuitry is the layer-based organization of specific cell types and synaptic inputs. Accordingly, cortical inhibitory interneurons (INs), which shape local network activity, exhibit subtype-specific laminar specificity of synaptic outputs. However, the underlying molecular mechanisms remain unknown. Here, we demonstrate that Immunoglobulin Superfamily member 11 (IgSF11) homophilic adhesion proteins are preferentially expressed in one of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Consistent with our previous work ( 52 , 53 ), the transplanted MGE progenitors produced morphologically identifiable ChCs that reside at the border between L1 and uL2/3 and develop synaptic cartridges apposed to AISs following their intrinsic developmental program. Our recent study showed that these transplanted ChCs express ChC markers and establish normal synapses on AISs electrophysiologically/ultrastracturally indistinguishable from those of endogenous ChCs ( 53 ). To further validate the identity of transplanted ChCs, we examined other properties of endogenous ChCs.…”
Section: Resultssupporting
confidence: 90%
“…Consistent with our previous work ( 52 , 53 ), the transplanted MGE progenitors produced morphologically identifiable ChCs that reside at the border between L1 and uL2/3 and develop synaptic cartridges apposed to AISs following their intrinsic developmental program. Our recent study showed that these transplanted ChCs express ChC markers and establish normal synapses on AISs electrophysiologically/ultrastracturally indistinguishable from those of endogenous ChCs ( 53 ). To further validate the identity of transplanted ChCs, we examined other properties of endogenous ChCs.…”
Section: Resultssupporting
confidence: 90%
“…Likewise in the cerebellum, Cdh7 mediates synapse formation between pontine axons and granule neurons ( Kuwako et al, 2014 ). More recently, IgSF11 has been identified as the homophilic adhesion molecule controlling synapse formation between inhibitory chandelier cells and pyramidal neurons in the cortex ( Hayano et al, 2021 ).…”
Section: Adhesive Functions Of Cams In Circuit Wiringmentioning
confidence: 99%
“…Consequently, global BT-IgSF-deficient mice displayed a moderately decreased excitatory synaptic strength in the dentate gyrus and long-term potentiation in hippocampal CA1 (Jang et al, 2015). In another study in neurons BT-IgSF was found to regulate the innervation of axons of chandelier cells on initial axon segments of pyramidal neurons (Hayano et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…So far, the function of BT-IgSF (IgSF11) has been studied in neurons, Sertoli and germ cells of the testes, during osteoclast differentiation and in the organization of pigment cells in fish (Ahi and Sefc, 2017; Chen et al, 2021; Eom et al, 2012; Hayano et al, 2021; Jang et al, 2015; Kim et al, 2020; Pelz et al, 2017; Singh and Nusslein-Volhard, 2015). Knockdown studies using cultured mouse hippocampal neurons indicated that BT-IgSF is implicated in synaptic transmission through a tripartite interaction with PSD95 and AMPA receptors (Jang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%